ӘДЕБИЙ ШЫҒАРМАЛАРДА КЕЛБЕТЛИКЛЕРДИҢ СТИЛЬЛИК ХЫЗМЕТИ (инглис ҳәм қарақалпақ тили материаллары тийкарында) - Мухаммадияров, А. (SCIENCE and SOCIETY, 2023)
The article deals with the function and role of adjectives in the disclosure of images in English and Karakalpak literary works separately based on the linguocultural aspect.
Keywords: literary character; linguocultural aspect; adjective; the role of adjectives; describe; lexical meaning; affix; the activeness of affixes; original adjective; adjectives in English and Karakalpak languages